Incorporating patient safety into early undergraduate medical education: teaching medical students to perform surgical time outs during anatomy. Issue 1 (16th March 2021) - Suleiman, Abdul-Rahman M; Amarasinghe, Daniel; Kathuria, Priya; Vandel, Jacob; Holloway, Jordan; Elkin, Kenneth; Walker, Paul; Levine, Diane
Abstract : Objectives: To introduce surgical safety checklists and time outs to future physicians through early incorporation of time outs in the first year gross anatomy course. Setting: The Wayne State University School of Medicine Anatomy Lab. Participants: Approximately 300 first year medical students per year participated in the intervention. Interventions: An educational presentation on medical errors focusing on surgical errors was developed. Students in 2017–2018 viewed the presentation and completed two time outs, one with the first anatomy dissection and a second with the last dissection. Preintervention and postintervention surveys were completed and results compared. Students completed a second postintervention survey after the second time out. Students in 2018–2019 were asked to complete the time outs before every dissection. Time out procedure sheets were collected to determine completion rates. The intervention was further modified for academic year 2019–2020 and time out sheets were again collected. Outcome measures: Four domains of learning were surveyed: (1) major components and goals/limitations of universal protocol, (2) medical error lexicon, (3) components of a time out, and (4) confidence in completing time out checklists. Results: Postintervention surveys demonstrated significant improvement in each domain. Students found time outs easy to complete and developed confidence in performing time outs. Following a successful pilot, time outs were incorporated into every dissection. Students continued to perform this procedure despite absence of adverse consequences for not doing so. Conclusion: Students found the time outs easy to complete and developed the confidence and ability to perform a surgical time out early in their medical education. The new skills, knowledge and attitudes that these medical students have developed will hopefully improve the care they provide to patients, thereby advancing the practice of quality improvement and patient safety in the clinical setting.